Access to multi-functionalized oxazolines via silver-catalyzed heteroannulation of enamides with sulfoxonium ylides - Liu, Rui-Hua (2022)
Disclosed herein is an efficient Ag-catalyzed [4 + 1] heteroannulation reaction of enamides with α-carbonyl sulfoxonium ylides. The diastereoselective transformation provides a practical access to a diverse range of multi-functionalized oxazoline derivatives. The synthetic utility of the resultant tetra-substituted oxazolines is further demonstrated by a series of useful manipulations into valuable building blocks of pharmaceutical relevance.